Generational transfer and social sustainability in the dairy sheep farms of the Basque country - Ramos Truchero G. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
Generational transfer in family farms is a vital factor for the social sustainability of livestock production systems. This sustainability is threatened, not because globalization will eventually put an end to small-scale agriculture, as predicted by certain authors, but simply because many younger members of farming families no longer decide to take up farming. The aim of this paper is to present and to explain, from a sociological perspective, the reasons and the social processes that drive young people either to abandon livestock farming or to remain in the sector. To that end, the context of dairy sheep farming is examined in the Basque Country and the decisions taken by the younger members of farming families with first-hand experience of the problems surrounding succession. A qualitative approach is chosen in which 24 in-depth interviews were conducted with the younger members of farming families. The results show, first of all, the existence of a complex set of factors and discourses framed in the context of post-modern agrarian society. Furthermore, our analysis reveals the presence of four different profiles and social discourses among the younger members of farming families facing the problem of succession.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)